PEMANFAATAN PUPUK ORGANIK PADA BUDIDAYA TANAMAN BAWANG MERAH DI NAGARI PALANGKI KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Delvi Yanti; Fadli Irsyad; Imelda Safitri (Jurnal Hilirisasi IPTEKS, 2023)
The factors influencing shallot production include the soil nutrient content. Efforts to increase shallot production can be achieved through optimal fertilizer usage. The use of inorganic fertilizers can disrupt the biological ecosystem balance of the soil. To address this, the utilization of organic fertilizers becomes essential as they are more environmentally friendly and utilize existing waste. Nagari Palangki, known for having the largest livestock market in West Sumatra, generally has a substantial number of livestock owners, thus having significant potential in providing organic fertilizer. The availability of organic fertilizer should support agricultural activities, especially shallot cultivation, in Nagari Palangki. Based on this premise, it's crucial to conduct education among the community regarding the utilization of organic fertilizer in shallot cultivation in Nagari Palangki. The activity aims to transfer knowledge to the community to enhance shallot production in Nagari Palangki, IV Nagari District, Sijunjung Regency. The target audience comprises the community involved in shallot cultivation. The implementation of activities related to the use of organic fertilizers in shallot cultivation in Nagari Palangki has been completed. The farming community responded positively to the knowledge transfer, with farmers even applying the materials given to their land. Furthermore, the waste from the livestock market in Nagari Palangki, IV Nagari District, Sijunjung Regency, holds substantial potential and supports the success of the shallot cultivation encouraged by the local government of Nagari Palangki.